2024
DOI: 10.1007/s43979-024-00084-w
|View full text |Cite
|
Sign up to set email alerts
|

Increasing heat pump adoption: analysing multiple perspectives on preparing homes for heat pumps in the UK

Ned Lamb,
David Elmes

Abstract: Heat pumps are a solution for decarbonising home heating in the UK. However, the readiness of UK homes for heat pumps is an area of concern regarding the policies aimed at increasing heat pump adoption. This work combines multiple perspectives in evaluating the technical readiness of homes with the market readiness of installers and homeowners to proceed with installing heat pumps. The effectiveness of past heating and energy efficiency policies in the UK are reviewed, along with building regulations, incentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…2,14,15 For example, in their recent systematic review of developments in national heat pump markets, Gaur et al 13 identified a range of regulatory, economic, structural, and infrastructure barriers, in addition to issues of social acceptance. In the UK context, Lamb and Elmes 16 recently estimated the technical and market readiness of UK households for adopting heat pumps to be 34.7% and 11.1%, respectively, while awareness of sustainable heating technologies remains low. 17…”
Section: Introductionmentioning
confidence: 99%
“…2,14,15 For example, in their recent systematic review of developments in national heat pump markets, Gaur et al 13 identified a range of regulatory, economic, structural, and infrastructure barriers, in addition to issues of social acceptance. In the UK context, Lamb and Elmes 16 recently estimated the technical and market readiness of UK households for adopting heat pumps to be 34.7% and 11.1%, respectively, while awareness of sustainable heating technologies remains low. 17…”
Section: Introductionmentioning
confidence: 99%